WHAT IF RUSSIA SHUT OFF UKRAINE’S GAS AGAIN? A COMPUTABLE GENERAL EQUILIBRIUM MODEL - P. BARRY, Michael (CENTRAL ASIA AND THE CAUCASUS, 2014)
This paper asks the question: what would happen to the economies of the world should Russia completely shut off natural gas shipments to the Ukraine. Significant findings of this model include the following:The impact of the gas shutoff is overwhelmingly concentrated in Ukraine and Russia, whose economies would suffer GDP declines of 2.47 percent and 2.16 percent, respectively. Perhaps surprisingly, the model suggests Eastern Europe would experience only a small decline in GDP (0.13 percent) and Western Europe’s GDP would be unaffected. The GDP of gas-pruducing republics of the Other Former Soviet Union (FSU), major gas suppliers through the Russian pipelines, would decline by 0.75 percent.While the impacts to overall GDP are possibly smaller than expected, effects to individual industry sectors in many countries are quite large. One response of Ukraine and Europe to the cessation of Russian gas is an attempt to replace supplies with domestically produced gas. While output of natural gas decreases by 4.86 percent in Russia and 11.6 percent in the Rest of the Former Soviet Union, gas production increases in Ukraine, Eastern Europe, and Western Europe by 140.1 percent, 88.1 percent, and 12.0 percent, respectively (though note that each region starts with a small base). Production of natural gas increases in Africa (6.9 percent), the Middle East (5.2 percent), the United States (2.0 percent), and the Rest of the World (2.2 percent). Industry sectors within the Ukraine are forced to adjust to the decrease in gas imports. While output of Ukrainian domestic gas increases by 140.1 percent, Ukrainian output of many sectors significantly decrease, including Heavy Manufacturing (–12.5 percent), Light Manufacturing (–5.3 percent), Utilities and Construction (–5.0 percent), capital goods (–4.7 percent), and processed food (–2.4 percent).While Russia suffers a major decline in its massive gas industry (–4.9 percent), the domestic surplus of gas provides for cheaper production in other Russian industries. Russian output in several sectors significantly increases, including that in Heavy Manufacturing (3.9 percent), Light Manufacturing (3.1 percent), Oil (1.0 percent), and extraction (1.5 percent). Perhaps surprisingly, other than in natural gas production, the industry sectors of Eastern and Western Europe do not experience significant changes.The gas shutoff decreases gas supply in several regions, resulting in significantly higher gas prices, including those in Ukraine (27.6 percent price increases), Eastern Europe (14.5 percent), and Western Europe (4.7 percent). Greater supplies lower prices in Russia (–5.0 percent) and the other gasproducing republics of the FSU (–3.6 percent).A shutoff of Russian gas would directly result in a decrease of aggregate gas imports by volume to Ukraine (–48.3 percent or –$3.4 billion), Eastern Europe (–33.8 percent or –2.1 billion), and Western Europe (–2.9 percent or –1.1 billion).Russia’s shutting off gas to Ukraine would hurt Russia the most, with a net welfare loss to Russia of $11.8 billion. Other large welfare losses would accrue to Ukraine (–$722 million), Eastern Europe (–$469 million), and Western Europe (–$1.37 billion).